Seismic performance of cold formed steel walls sheathed by fibre-cement board panels. (April 2015) - Zeynalian, Mehran; Ronagh, H.R.
Abstract: This paper presents an experimental study of cold formed steel frames sheathed by fibre-cement boards (FCB) under cyclic lateral loading. Four full scale fibre-cement shear walls were tested. Of particular interests are the specimens maximum lateral load capacity and the load–deformation behaviour as well as a rational estimation of the seismic response modification factor, R factor. The study also looks at the failure modes of the systems and investigates the main factors contributing to the ductile response of the CFS shear walls in order to suggest improvements so that the FCB sheathed walls respond plastically with a significant drift and without any risk of brittle failure such as connection failure or fibre-cement board fracture. Both double-sided and single-sided FCB shear panels as well as a new proposed configuration were studied. The study shows that while the overall performance of the currently in-use FCB sheathed lateral resistant system under cyclic loads is not satisfactory with a small average R factor of 2.5, the proposed FCB lateral resistant system can be considered as a reliable system with a much higher value of R factor of 5. Highlights: Lateral performance of Cold Formed Steel Walls Sheathed by Fibre-Cement Board Panels. Experimental tests on seismic performance of Cold Formed Steel Walls Sheathed by Fibre-Cement Board Panels. Response modification factor, R factor, of Cold Formed Steel Walls Sheathed by Fibre-Cement Board Panels. Prescribed R factor for Fibre-Cement Board Sheathed CFS system in AISI and AS4600 should be revised.